1997
DOI: 10.1021/jp9638797
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Study of Ozone Adsorption on CaO

Abstract: Ozone adsorption on CaO pretreated at different temperatures was studied by FTIR spectroscopy at 77−300 K. Besides physisorption effects, a weak complex was observed formed by ozone molecules with the OH surface groups, which have pronounced basic properties, as shown by a downward shift of the νOH band by about 21 cm-1 and by slight changes in ozone vibrational frequencies. Chemisorption of O3 occurred on CaO activated at 973 K as evidenced by the appearance of a band at 812 cm-1 accompanied by two weaker pea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
38
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 18 publications
5
38
0
Order By: Relevance
“…These strong sites enhance gaseous ozone decomposition, generating active atomic oxygen (O • ), as previously reported [26,29,40,41]. Hence, the generation of a high number of active atomic oxygen species [33][34][35][36][37] could be responsible for the catalytic ozonation of toluene in a new kind of advanced oxidation process. oxygen species, leading to the observed decrease in the reaction rate of toluene catalytic oxidation (see Figure 3).…”
Section: Catalytic Ozonation Using Natural and Modified Zeolites At 2mentioning
confidence: 56%
See 1 more Smart Citation
“…These strong sites enhance gaseous ozone decomposition, generating active atomic oxygen (O • ), as previously reported [26,29,40,41]. Hence, the generation of a high number of active atomic oxygen species [33][34][35][36][37] could be responsible for the catalytic ozonation of toluene in a new kind of advanced oxidation process. oxygen species, leading to the observed decrease in the reaction rate of toluene catalytic oxidation (see Figure 3).…”
Section: Catalytic Ozonation Using Natural and Modified Zeolites At 2mentioning
confidence: 56%
“…Several studies have reported the role of Lewis acid sites on the generation of active atomic oxygen species. Such species could react with adsorbed toluene on the surface of zeolite samples, as represented by Equation (2) [33][34][35][36][37]. Figure 3 shows the influence of the density of strong Lewis acid sites on the reaction rate of toluene ozonation using natural and modified zeolite as catalysts.…”
Section: Catalytic Ozonation Using Natural and Modified Zeolites At 2mentioning
confidence: 99%
“…As observed by several authors [53][54][55] stabilizing on basic surface sites, which rapidly forms surface peroxide and superoxide ions.…”
Section: Coupling Non Thermal Plasma To Catalysismentioning
confidence: 71%
“…A number of studies have been performed on the adsorption of O 3 onto various mineral oxides, using electron paramagnetic resonance, infrared spectroscopy and kinetic measurement techniques (Dhandapani and Oyama, 1997). The surfaces examined were among others: γ -Al 2 O 3 (Klimovskii et al, 1983;Bulanin et al, 1995a;Thomas et al, 1997), SiO 2 (Bulanin et al, 1994), TiO 2 (Bulanin et al, 1995a(Bulanin et al, , 1995b, CaO (Bulanin et al, 1997) and MgO (Bulanin et al, 1995a;Berlier et al, 2002). A few semi-quanitative studies on the interaction between ozone and authentic mineral dust have been published (Suzuki et al, 1979;Alebic-Juretic et al, 1992;Alebic-Juretic et al, 2000), and initial uptake coefficients for O 3 uptake onto synthetic and authentic minerals have been measured (Michel et al, 2002).…”
Section: Introductionmentioning
confidence: 99%